Evaluation of (Neutrophil-to-lymphocyte Ratio (NLR)) as an Inflammatory Immune Marker in Patients with Acute Infections and Comparison- with Healthy Subjects - Entiha Abdul-Zahra Abdul-Kareem (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Inflammation is a fundamental biological response in infectious diseases involving alterations in circulating immune cells, particularly neutrophils and lymphocytes. Specific Background: The neutrophil-to-lymphocyte ratio (NLR), derived from routine complete blood count testing, reflects the balance between innate and adaptive immunity and is increasingly utilized in clinical evaluation. Knowledge Gap: Despite its clinical use, further validation of NLR as a reliable inflammatory immune marker in acute infections compared with healthy individuals remains necessary. Aims: This study aimed to evaluate NLR as an inflammatory immune marker in patients with acute infections and compare findings with healthy controls. Results: The study included 30 patients and 20 controls. Patients demonstrated significantly higher absolute neutrophil count (8.49 ± 1.58 vs. 3.83 ± 0.88), markedly elevated NLR (10.62 ± 3.26 vs. 1.67 ± 0.45), and reduced absolute lymphocyte count (0.86 ± 0.27 vs. 2.37 ± 0.45) (p < 0.001). ROC analysis showed excellent diagnostic performance, with NLR and neutrophil count achieving an AUC of 1.000, and lymphocyte count an AUC of 0.995. Correlation analysis revealed positive association between neutrophils and NLR and negative association between lymphocytes and NLR. Novelty: This study provides integrated statistical and diagnostic validation of NLR using hematological indices and ROC analysis within a defined cohort. Implications: NLR represents a simple, low-cost, and accessible biomarker for assessing inflammatory and immune responses in acute infections and may support clinical evaluation and disease monitoring. Highlights:• Marked Elevation of Neutrophils Alongside Reduced Lymphocytes Identified in Infected Individuals• Diagnostic Analysis Demonstrated Near-Perfect Classification Accuracy Between Groups• Correlation Patterns Confirmed Ratio Structure Driven by Opposing Hematological Components Keywords: Neutrophil Lymphocyte Ratio, Acute Infection, Inflammatory Marker, Complete Blood Count, Biomarker